Selective Chemical Substitution of Cu in the Structure of TiAl3 Type InPd3: Experimental and Theoretical Studies. Issue 26 (31st August 2022) - Roy, Nilanjan; Kuila, Sandip K.; Harshit,; Pramanik, Parna; Jana, Partha P.
Abstract: InPd3‐x Cux (x=0–1) were prepared by high temperature synthesis starting from the highly pure constituent elements. The crystal structures were determined by X‐ray diffraction. In the structure of InPd3‐x Cux (x=0–1), Cu stabilizes the TiAl3 ‐type InPd3 and selectively substitutes one of the two Pd positions and at the limiting composition ordered InPd2 Cu is formed where Cu completely occupies that position. The intriguing selective substitution was investigated by first‐principles total energy calculations followed by electronic structure and chemical bonding analysis. Abstract : In InPd3‐x Cux (x=0‐1), Cu stabilizes the TiAl3 ‐type InPd3 and selectively substitutes one of the two available Pd positions. At the limiting composition, Cu completely occupies that position and ordered InPd2 Cu is formed. This substitution pattern has been investigated by combinations of both X‐ray diffraction and electronic structure calculations.